Impact of schools on student performance. A study based on the ÜGK 2016 survey - Petrucci, Franck; Ambrosetti, Alice; Crotta, Francesca; Nidegger, Christian (Swiss Journal of Educational Research, 2020)
According to the school effectiveness research stream, students’ performance depends on their individual characteristics and their schooling context. To what extent can the ÜGK survey, a large-scale assessment carried out at the Swiss level, provide the cantons with information for judging their schools’ effectiveness ? In Ticino and Geneva, the proportion of differences in results linked to the school appears to be extremely modest. Value added calculations show that the vast majority of schools achieve results in line with those that can be expected. Only a few have lower than expected results, but no link between their underperformance and their students’ population demographic can be established.